Clear Improvement in Real-World Chronic Myeloid Leukemia Survival: A Comparison With Randomized Controlled Trials - Vener, Claudia; Rossi, Silvia; Minicozzi, Pamela; Marcos-Gragera, Rafael; Poirel, Hélène A.; Maynadié, Marc; Troussard, Xavier; Pravettoni, Gabriella; De Angelis, Roberta; Sant, Milena; , the EUROCARE-6 Working Group; Hackl, M.; et al. (Frontiers in Oncology, 2022)
Tyrosine kinase inhibitors (TKIs) have been improving the prognosis of chronic myeloid leukemia (CML) patients, but there are still large differences in survival among European countries. This raises questions on the added value of results from population-based studies, which use real-world data, compared to results of randomised controlled trials (RCTs) involving CML patients. There are also questions about the extent of the findings on RCTs effectiveness for patients in the general population. We compare survival data extracted from our previous systematic review and meta-analysis of CML RCTs with the latest updated population-based survival data of EUROCARE-6, the widest collaborative study on cancer survival in Europe. The EUROCARE-6 CML survival estimated in patients (15-64 years) diagnosed in 2000-2006 vs 2007-2013 revealed that the prognostic improvement highlighted by RCTs was confirmed in real-world settings, too. The study shows, evaluating for the first time all European regions, that the optimal outcome figures obtained in controlled settings for CML are also achievable (and indeed achieved) in real-world settings with prompt introduction of TKIs in daily clinical practice. However, some differences still persist, particularly in Eastern European countries, where overall survival values are lower than elsewhere, probably due to a delayed introduction of TKIs. Our results suggest an insufficient adoption of adequate protocols in daily clinical practice in those countries where CML survival values remain lower in real-life than the values obtained in RCTs. New high-resolution population-based studies may help to identify failures in the clinical pathways followed there.